Relationship of Helicobacter pylori Infection with Nonalcoholic Fatty Liver Disease: A Meta-Analysis. (25th January 2023) - Xu, Guangqin; Ma, Shaoze; Dong, Liyan; Mendez-Sanchez, Nahum; Li, Hongyu; Qi, Xingshun
Abstract : Background and Aims . Helicobacter pylori ( H. pylori ) and nonalcoholic fatty liver disease (NAFLD) have become increasingly recognized, both of which affect human health globally. The association of H. pylori infection with NAFLD remains unclear. Methods . PubMed, EMBASE, and Cochrane Library databases were searched. Only a random-effects model was used. Odds ratios (ORs) and risk ratios (RRs) with 95% confidence intervals (CIs) were calculated for the combined estimates of raw data. Adjusted ORs (aORs) and hazard ratios (aHRs) with 95% CIs were calculated for the combined estimates of data adjusted for confounders. Results . Thirty-four studies with 218573 participants were included. Based on unadjusted data from 26 cross-sectional studies and 3 case-control studies, H. pylori infection was significantly associated with the presence of NAFLD (OR = 1.26, 95% CI = 1.17–1.36, P < 0.001 ). Based on adjusted data from 15 cross-sectional studies and 1 case-control study, H. pylori infection was significantly associated with the presence of NAFLD (aOR = 1.25, 95% CI = 1.08–1.44, P < 0.001 ). Compared with control subjects without NAFLD, patients with moderate (OR = 1.67, 95% CI = 1.17–2.39, P = 0.005 ) and severe (OR = 1.71, 95% CI = 1.30–2.24, P < 0.001 ) NAFLD, but not those with mild NAFLD (OR = 1.14, 95% CI = 0.9–1.45, P = 0.286 ), had significantly higher proportions of H. pylori infection. The association of H. pylori infection with the occurrence of NAFLD was statistically significant based on adjusted data from 3 cohort studies (aHR = 1.18, 95% CI = 1.05–1.34, P = 0.007 ), but not based on unadjusted data from 3 cohort studies (RR = 1.41, 95% CI = 0.80–2.48, P = 0.237 ). Conclusion . H. pylori infection is associated with NAFLD, especially moderate and severe NAFLD. The impact of H. pylori eradication on the prevention of NAFLD should be further explored.